THTHE SCIENTIFIC AND METHODOLOGICAL INTERPRETATION OF THE CONCEPT OF DEVELOPING OF READING COMPETENCE OF PUPILS IN FOREIGN LANGUAGE EDUCATION - Erkulova Feruza Melikuziyevna,; Ismoilova Oygul Abdiqaxxorovna, (Ustozlar uchun, 2025)
Reading competence is a fundamental aspect of foreign language education,playing a key role in the development of communicative skills and academic success .This article explores the scientific and methodological interpretation of the concept of developing of reading competence among pupils in English as a foreign language .Using a mixed-methods approach ,the study includes theoretical analysis ,surveys of teachers and students and classroom observations .The study was conducted among 29  9th grade students at a rural secondary school in Uychi district in Namangan region of Uzbekistan.The pupils were divided into 2 groups ,the control group and the experimental one. Results indicate that traditional translation –based reading instruction remains common,while many students struggle with vocabulary ,comprehentionand motivation.However, when exposed to interactive and strategy-based reading tasks ,students demonstrate noticeable improvement in understanding and engagement .The study concludes that a well-structured methodological framework ,focused on learner needs ,text authenticity and skill integration ,is essential for effectively fostering reading competence in foreign language classrooms.